Comparative Analysis of the Transfer of Wali Aqrab to Wali Ab'ad According to Kitabun Nikah with the Opinion of Imam Malik - Fadhil, Muhammad; Fajri, Muhammad; Hafidzi, Anwar (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT The discussion about the transfer of marriage guardians in marriage is about whether things are permissible or not. This is important to know because it will affect the validity of the marriage contract. Based on the same text, between the book of marriage written by Sheikh Muhammad Arsyad Al-Banjari the Imam Sya'fii school, states that the guardian is one of the pillars of marriage that must exist and the legal requirements are fulfilled, then the transfer of the guardian aqrab to the guardian ab'ad is in accordance with the shar'i legal procedures. which is good and right, while Imam Malik stated that the guardian of the person who was present at the wedding contract, so that the transfer of the guardian aqrab to the guardian ab'ad can be through a will. This research tries to reveal the background and thoughts of Sheikh Muhammad Arsyad Al Banjari contained in the marriage book with the Maliki school of thought. Keywords: Marriage Guardian, Marriage Book, Imam Malik ABSTRAK Pembahasan tentang perpindahan wali nikah dalam perkawinan adalah tentang apakah hal yang dibolehkan atau tidak. Ini penting untuk diketahui karena akan mempengaruhi keabsahan akad nikah. Berdasarkan teks yang sama, antara kitabun nikah yang dikarang oleh Syekh Muhammad Arsyad Al-Banjari dan Imam Maliki memiliki pemikiran yang berbeda. Dalam kitabun nikah yang pengarangnya bermadzhab imam Sya'fii menyatakan bahwa wali merupakan salah satu rukun nikah yang harus ada dan persyaratan hukumnya terpenuhi baru dapat berpindah dalam perwalian tersebut, dengan hal itu perpindahan wali aqrab ke wali ab'ad telah sesuai prosedur hukum syar'i yang baik dan benar, sementara Imam Malik menyatakan bahwa wali orang yang hadir pada akad pernikahan, sehingga perpindahan wali aqrab ke wali ab'ad bisa dapat melalui wasiat. Penelitian ini mencoba mengungkap latar belakang dan hasil pemikiran dari Syekh Muhammad Arsyad Al Banjari yang terdapat dalam kitabun nikah dengan madzhab Maliki. Kata Kunci : Wali Nikah, Kitabun Nikah, Imam Malik